Heart Electrical Instabilities: Some Mechanisms by Topology, Symmetry, Spin, Semiotics; Diagnosis (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: heart electrical instability; mathematical modeling; diagnosis